(untitled) (Journal of NELTA, 2014)
This study examined 1) undergraduates’ learning achievement in a fundamental English course that included activities with a Facebook group; 2) the level of students’ attitudes toward learner autonomy; and 3) the level of their attitudes toward Facebook use in an English course. The subjects in the study were first-year undergraduate students that had registered for fundamental English course at King Monkut’s University, North Bangkok (KMUTNB). They were selected using the convenience sampling method, and were organized into an experimental group. Students were provided with additional activities or homework with the Facebook group. The results indicated that the students’ learning achievement was not in accordance with the efficiency criterion and the levels of their attitudes toward learner autonomy during the three phases studied were significantly different. However, the students’ attitudes toward integrating Facebook into an English course were found to be positive. DOI: http://dx.doi.org/10.3126/nelta.v18i1-2.10335 Journal of NELTA, Vol 18 No. 1-2, December 2013; 115-132